Impact of Employee Placement, Motivation, and Career Development on Performance and Productivity at Bank XYZ Using PLS-SEM - Nadya Amelia Khumaira; Moch. Tutuk Safirin (Advance Sustainable Science Engineering and Technology, 2025)
The role of employees is crucial in achieving the company's goals, as employees perform various activities from input to output in customer service. The purpose of this research is to determine the influence of employee placement, motivation, and career development variables on employee performance and employee productivity at Bank XYZ. This research employs the PLS-SEM method implemented using the statistical software SmartPLS. The results of this study show that the employee placement variable has p-values of 0.033 and t-values of 2.137 on the employee performance variable. The employee placement variable has p-values of 0.819 and t-values of 0.229 on employee productivity. The motivation variable has p-values of 0.000 and t-values of 4.141 on employee performance. The motivation variable has p-values of 0.027 and t-values of 2.217 on employee productivity. The career development variable has p-values of 0.395 and t-values of 0.851 on employee performance. The career development variable has p-values of 0.688 and t-values of 0.402 on employee productivity. The employee performance variable has p-values of 0.000 and t-values of 4.273 on employee productivity.